Micromechanism Underlying Nonlinear Stress-Dependent K0 of Clays at a Wide Range of Pressures - Xiang-yu Shang; Chen Yang; Guo-qing Zhou; Xiu-zhong Zheng (Advances in Materials Science and Engineering)
In order to investigate the mechanism underlying the reported nonlinear at-rest coefficient of earth pressure, K0 of clays at high pressure, a particle-scale model which can be used to calculate vertical and horizontal repulsion between clay particles has been proposed. This model has two initial states which represent the clays at low pressure and high pressure, and the particles in this model can undergo rotation and vertical translation. The computation shows that the majority of particles in a clay sample at high pressure state would experience rotation during one-dimensional compression. In addition, rotation of particles which tends to form a parallel structure causes an increase of the horizontal interparticle force, while vertical translation leads to a decrease in it. Finally, the link between interparticle force, microstructure, and macroscopic K0 is analyzed and it can be used to interpret well the nonlinear changes in K0 with both vertical consolidation stress and height-diameter ratio.